Land Rights as Security for Materials - Dewi, Inggrid Kusuma (Inspiring Law Journal, 2024)
Article 14 paragraph (3) of the Mortgage Rights Law states "The Mortgage Rights Certificate as referred to in paragraph (2) has the same executive power as a court decision that has obtained permanent legal force and is valid as a substitute for the grosse acte Hypotheek as far as it concerns land rights". The definition of executive power can be interpreted as "the right to sell the object of the mortgage right with one's own authority which is one manifestation of the priority position held by the mortgage right holder or the first mortgage right holder in the event that there is more than one mortgage right holder. The right is based on the promise of the mortgage right grantor that if at any time the debtor defaults, the mortgage right holder has the right to sell the mortgage right object by means of a public auction